Assessment of resources and services available in Sri Lankan health libraries to facilitate practice of Evidence-Based Medicine - Sritharan, T. (The Library, University of Colombo, 2019)
The best available evidence plays a key role in informed decision making of clinical situations and in the successfulness of Evidence-Based Medicine (EBM) approaches. Medical literature is a part of clinical decision making of medical professionals and successfulness of EBM. The objective of this study was to assess the resources and services available in Sri Lankan health libraries to facilitate practice of EBM. The survey research design was used to collect data from 26 health libraries which provide health information resources and services exclusively for health professionals. Out of 26 questionnaires 20 were returned at the rate of 77%. The results of the study showed that 85% (17) of the Sri Lankan health librarians acknowledged the concept and importance of EBM approaches. The majority of the health science libraries (75%) provide support for EBM practices, even though they do not have sufficient resources and specialized departments or sections specifically related to EBM. 65% (13) of the health libraries support systematic reviews by searching for literature. The identified major issues in providing EBM are lack of resources (70%) and unavailability of trained staff (85%) to cater for the needs related to practice of EBM. All health librarians are interested in attending training programs on EBM support services. Subscription for best evidence based resources on consortium basis and training programs for health information professionals to support EBM practice were the valuable suggestions made by the participants. This study concludes that the resources and services available in Sri Lankan Health Libraries to facilitate EBM practice are scarce. Only basic or limited services such as literature searching are provided by them. The role of health librarians is very important in EBM practices. Therefore, it is recommended to acquire more evidence-based medical resources as the EBM requires acquisition and use of a complex set of skills, including the ability to locate and critically evaluate clinical relevant research literature. All health librarians should be specially trained in acquiring and providing evidence-based resources, as the availability of “relevant information” is most critical for safeguarding lives and raises the quality of medical services as well as the satisfaction of the health professionals.
Keywords: Evidence-Based Medicine, evidence based resources, health information, health information provision, health science libraries